Lavandula gibsoni and plectranthus mollis essential oils: chemical analysis and insect control activities against aedes aegypti, anopheles sfttephensi and culex quinquefasciatus - Kulkarni, Roshan R.; Pawar, Pushpa V.; Joseph, Mary P.; Akulwad, Ambadas K.; Sen, Avalokiteswar; Joshi, Swati P. (Journal of Pest Science, 2013)
Essential oils and acetone extracts from Lavandula gibsoni and Plectranthus mollis, family Lamiaceae, were investigated for their mosquito larvicidal activity against 4th instar larvae of Aedes aegypti, Anopheles stephensi and Culex quinquefasciatus. LC50 values against these three species were 48.3, 62.8 and 54.7 mg/L for L. gibsoni essential oil and 118.5, 137.2 and 128.1 mg/L, respectively, for its acetone extract, while LC50 values for P. mollis essential oil were 25.4, 33.5 and 29.5 mg/L and 195.0, 213.8 and 209.0 mg/L, respectively, for its acetone extract. Repellence of the essential oils was assessed against A. aegypti adults. L. gibsoni essential oil provided 100 % protection for more than 7 h at a concentration of 2.0 mg/cm(2). Under the same conditions, the standard repellent N,N-diethyl-meta-toluamide, at 0.25 mg/cm(2), provided 100 % protection for more than 8 h, while P. mollis essential oil was only weakly repellent. The major components from both essential oils were identified based on GC-MS analysis and linear retention indices. Our results demonstrated promising larvicidal activities of both essential oils against these mosquito species. L. gibsoni essential oil also showed promising repellent activity.
Keywords: Essential oil; Lavandula gibsoni; Mosquito larvicidal activity; Mosquito repellent; Plectranthus mollis